10x(x+17)=

Simple and best practice solution for 10x(x+17)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x(x+17)= equation:


Simplifying
10x(x + 17) = 0

Reorder the terms:
10x(17 + x) = 0
(17 * 10x + x * 10x) = 0
(170x + 10x2) = 0

Solving
170x + 10x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '10x'.
10x(17 + x) = 0

Ignore the factor 10.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(17 + x)' equal to zero and attempt to solve: Simplifying 17 + x = 0 Solving 17 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + x = 0 + -17 Combine like terms: 17 + -17 = 0 0 + x = 0 + -17 x = 0 + -17 Combine like terms: 0 + -17 = -17 x = -17 Simplifying x = -17

Solution

x = {0, -17}

See similar equations:

| (-0.3)(2.7)= | | a+8=b | | 3x-26=x-2 | | 7x(3+20)= | | z^2-(3+3i)z+5i=0 | | z^2(3+3i)z+5i=0 | | L=8-4b | | 6n-17=10n+47 | | -8=4l | | 5x-20(4-x)=120 | | 20+6x=-2x+28 | | 4x-.76=3(x-.03) | | 15x+24=8(10-3x)-2 | | 4y=-17y-4 | | 3(2x+3)=5(2x+1) | | 0.30x+.05(18-x)=.10(-16) | | -.5(x-6)+.5(x+2)=x-9 | | -3x-y=-6+7y | | 4(3x-2)=88 | | 26x-19=113-6x | | 6x^2+6x-8=0 | | -32a^6-28a^5-36a= | | 4p^2-2+9= | | a=.5bc | | 0=x^2-11x-5 | | -x+7=y | | 6(2x-3)=3(4x+4) | | 3p-18=4p-4 | | 5x+8-11x=5x-(3x+16) | | 4x-12=2x+10 | | (2x+28)+2y=60 | | (2x+14)+2y=60 |

Equations solver categories